In vivo Observation of Tree Drought Response with Low-Field NMR and Neutron Imaging - Malone, Michael W.; Yoder, Jacob; Hunter, James F.; Espy, Michelle A.; Dickman, Lee T.; Nelson, Ron O.; Vogel, Sven C.; Sandin, Henrik J.; Sevanto, Sanna (Frontiers in Plant Science, 2016)
Using a simple low-field NMR system, we monitored water content in a living tree in a greenhouse over two months. By continuously running the system, we observed changes in tree water content on a scale of half an hour. The data showed a diurnal change in water content consistent both with previous NMR and biological observations. Neutron imaging experiments show that our NMR signal is primarily due to water being rapidly transported through the plant, and not to other sources of hydrogen, such as water in cytoplasm, or water in cell walls. After accounting for the role of temperature in the observed NMR signal, we demonstrate a change in the diurnal signal behavior due to simulated drought conditions for the tree. These results illustrate the utility of our system to perform noninvasive measurements of tree water content outside of a temperature controlled environment.